Using meshes to change the characteristics of simulated rainfall produced by spray nozzles - Carvalho, Sílvia C. P. (2014)
Rainfall simulators have been used for many years contributing to the understanding of soil and water conservation processes. Nevertheless, rainfall simulators’ design and operation might be rather demanding for achieving specific rainfall intensity distributions and drop characteristics and are still open for improvement. This study explores the potential of combining spray nozzle simulators with meshes to change rainfall characteristics, namely drop properties (drop diameters and fall speeds). A rainfall simulator laboratory set-up was prepared that enabled the incorporation of different wire meshes beneath the spray nozzles. The tests conducted in this exploratory work included different types of spray nozzles, mesh materials (plastic and steel), square apertures and wire thicknesses, and positions of the meshes in relation to the nozzles. Rainfall intensity and drop size distribution and fall speed were analysed. Results showed that the meshes combined with nozzles increased the mean rainfall intensity on the 1 m2 control plot below the nozzle and altered the rain drops’ properties, by increasing the mass-weighted mean drop diameter, for example.